Identifying Opportunities for Tourism Cluster Development in Rural Communities - Baah-Kumi, Bernard (Journal of Tourism Management Research, 2021)
This work aims to identify economic opportunities for future tourism cluster development in tourism-dependent regions using the case of Taos County, New Mexico. The work analyzes the composition of local tourism economic activities of Taos County by quantifying how concentrated the tourism sector is in the county compared to the United States and the State of New Mexico from 2011 to 2019. The author analyzed data from the New Mexico Department of Tourism’s state and county tourism economic impact reports, the U.S. Bureau of Economic Analysis, and the U.S. Census Bureau using location quotients analysis. Results show that Taos has no high-performing, rising, high-potential tourism-related industry, despite the tourism sector providing a steady economic base for the community. The traveler accommodation industry, which is more concentrated in Taos than the state and the nation, is trending downwards. The arts, recreation and entertainment, transportation, and retail hold the potential for strength in the future, potentially contributing more to the county’s tourism economic base. The implication is that practitioners should work with groups of businesses in the tourism cluster instead of individual businesses to address their shared critical needs.